Sosialisasi Diet Rendah Gula dalam Penanganan Masalah Diabetes Mellitus di UGD Puskesmas Perawatan Biloro - Yerry Soumokil; Juleha Buton; Johora Mamulati (STIKes Ibnu Sina Ajibarang, 2023)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia associated with abnormalities in carbohydrate, fat and protein metabolism. A prominent complaint in patients with Diabetes Mellitus is that patients always feel weak and tire easily. Pharmacological actions are usually given insulin therapy and non-pharmacological therapy is used as a drug companion. One of the non-pharmacological therapies to reduce weakness and fatigue due to increased blood glucose is to apply a low-sugar diet. Where nurses provide low-sugar food and drinks while patients are in the ER and provide knowledge to patients and families about managing food and drinks independently for patients to consume while at home. The purpose of this application is to reduce blood glucose levels in diabetes mellitus patients at the Biloro Pearawatan Health Center. Writing the final report of this case study using a descriptive method with a nursing process approach and based on Evidence Based Practice. The analysis of this case study was carried out in 1 patient with diabetes mellitus with the focus of implementing a low-sugar diet intervention. The results after a low-sugar diet were found to result in a decrease in blood glucose levels in patients on the first day of 351 mg/dl and after being intervened for 3 days it showed a decrease in glucose levels to 207 mg/dl. Low sugar diet interventions can be given to other diabetes mellitus patients to reduce blood glucose levels.